A new vaccination approach for Salmonellosis employing a multi-epitope vaccine based on live microbial cell factory from Lactococcus lactis - Reyhaneh Sadat Moosavi-Kohnehsari; Mahnaz Jafari-Sohi; Tohid Piri-Gharaghie; Shakiba Tolou-Shikhzadeh-Yazdi; Mona Aghassizadeh-Sherbaf; Romina Hosseinzadeh (Poultry Science)
A major health and financial burden in the chicken sector is salmonella infection. It is difficult to create an oral vaccination that can provide strong intestinal mucosal immunity in birds, particularly cross-protection against several Salmonella serotypes. As a result, the poultry industry needs a powerful oral vaccination platform that uses live bacterial vectors to prevent various Salmonella serotypes. The genetically engineered L. lactis was given orally to birds as a vaccine after a multi-epitope vector was created using a reverse vaccinology technique. After the plasmid was digested, the target group produced a 72 kDa protein called multi-epitop. Birds that received the L. lactis/pNZ8121-Multi epitope vaccination showed increased levels of interferon (IFN-γ) and NFkB1α, increased transcription rates of cytokines, and a significant presence of IgY antibodies specific to the multi epitope gene in their serum. Salmonella infection is a severe health and economic burden in the poultry industry, according to spleen sections from the L. lactis/pNZ8121-Multi epitope. Developing an oral vaccine that can provide birds robust intestinal mucosal immunity—specifically, cross-protection against many Salmonella serotypes—is challenging. The results provide a fresh method for creating new immunological candidate multi-epitome genes by using the food-grade, non-pathogenic Lactococcus lactis as a protein cell factory. This method provides a unique technique to assess the long-term sustainability, cost, safety, and usefulness of experimental pharmaceutical products.